Estimating and analysing currency options implied risk-neutral density functions for the largest new EU member states - Olli Castrén (European Central Bank (ECB), 2005)
This paper uses data on currency options prices for the exchange rates of the three largest new EU member states Poland, Czech Republic and Hungary vis-à-vis the euro and the US dollar to estimate the risk-neutral density (RND) functions and the density interval bands. Analysing the RNDs, we find that only some of the implied moments on the Polish zloty exchange rate systematically move around policy events, while the implied moments on the RNDs on the Czech koruna and Hungarian forint show more systematic changes. Regarding the HUF/EUR currency pair, monetary policy news have a significant impact on all moments, while changes in implied standard deviation signal a higher probability of interest rate changes by the Hungarian central bank. The more marked results for HUF/EUR exchange rate could reflect the fixed exchange rate regime prevailing throughout the sample period.
Keywords: E52; F31; G15; 330; currency options data; Foreign exchange rate market sentiment; monetary policy news; Optionspreistheorie; Euro; US-Dollar; Schätzung; Polen; Tschechien; Ungarn; Statistische Verteilung